Flexible Metal–Organic Frameworks with Discriminatory Gate‐Opening Effect for the Separation of Acetylene from Ethylene/Acetylene Mixtures. Issue 27 (22nd June 2016) - Li, Libo; Krishna, Rajamani; Wang, Yong; Wang, Xiaoqing; Yang, Jiangfeng; Li, Jinping
Abstract : Adsorptive separation of acetylene from ethylene/acetylene mixtures is a technologically very important and highly challenging task. In this work, we describe two flexible metal–organic frameworks (MOFs), ELM‐11 and ELM‐13, that display adsorbate discriminatory gate effects. The two MOFs exhibit gate‐opening‐type adsorption properties for C2 H2 but not for C2 H4, leading to a highly selective adsorption of acetylene over ethylene at 273–298 K. The potential of the flexible MOFs for the separation is established by combining measurements of adsorption isotherms, ideal adsorbed solution theory (IAST) calculations of the adsorption equilibrium of the mixture, and transient breakthrough experiments. The results suggest the potential of both flexible MOFs for the industrial removal of acetylene from ethylene/acetylene mixtures through the energy‐efficient adsorption separation process. Abstract : Two flexible metal–organic frameworks (MOFs) exhibit gate‐opening‐type adsorption properties for acetylene but not for ethylene, leading to a highly selective adsorption of acetylene over ethylene at 273–298 K. The results suggest the potential of both flexible MOFs for industrial acetylene/ethylene separation through the energy‐efficient adsorption separation process.